A Challenging Combination: Anomalous Left Anterior Descending Coronary Artery, Myocardial Bridging, and Endothelial Dysfunction - El-Am, Edward A.; Corban, Michel T.; Pollak, Amy W.; Lerman, Amir; Ammash, Naser M. (Frontiers in Cardiovascular Medicine, 2020)
50 years old female patient with a medical history of hypertension presented to the clinic with chest pain, palpitations, and dyspnea on exertion of 2 years duration. Extensive workup in search of the culprit etiology of her chest pain revealed a challenging combination of an anomalous left anterior descending artery with myocardial bridging and endothelial dysfunction. She was treated medically with long acting nitrates, L-arginine and calcium channel blockers, and remains asymptomatic after 12 months of follow up.